2023
DOI: 10.1186/s41182-023-00521-z
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of health systems reform on COVID-19 control in Sierra Leone: a case study

Tracey Elizabeth Claire Jones-Konneh,
Angella Isata Kaikai,
Ibrahim Borbor Bah
et al.

Abstract: Background There are various impacts of COVID-19 on health systems of the world. The health systems of low- and middle-income countries are less developed. Therefore, they have greater tendencies to experience challenges and vulnerabilities in COVID-19 control compared to high-income countries. It is important to contain the spread of the virus, and likewise strengthen the capacity of health systems in order for the response to be effective and swift. The experience from 2014 to 2016 Ebola outb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…A previous study in Ethiopia found a 35% decline in under-five children’s services [ 20 ], and a significant drop in the use of reproductive, maternal, and newborn healthcare services [ 21 ]. COVID-19 has been shown to have an effect in previous studies, with 30% and 36% reductions in Sierra Leone and South Africa, respectively [ 22 , 23 ]. The COVID-19 pandemic could compromise vaccine delivery among under-five children, with an estimated 80 million children globally affected by disrupted immunization services and campaigns [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in Ethiopia found a 35% decline in under-five children’s services [ 20 ], and a significant drop in the use of reproductive, maternal, and newborn healthcare services [ 21 ]. COVID-19 has been shown to have an effect in previous studies, with 30% and 36% reductions in Sierra Leone and South Africa, respectively [ 22 , 23 ]. The COVID-19 pandemic could compromise vaccine delivery among under-five children, with an estimated 80 million children globally affected by disrupted immunization services and campaigns [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors reported that the fifth author’s name needed to be corrected from “Rei Takeuchi” to “Rie Takeuchi”.…”
mentioning
confidence: 99%